Stressed and not sleeping: poor sleep and psychological stress in elite athletes prior to the Rio 2016 Olympic Games - Halson, S. L.; Appaneal, R. N.; Welvaert, M.; Maniar, N.; Drew, M. K. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Psychological stress is reported to be an important contributor to reduced sleep quality and quantity observed in elite athletes. The purpose of this study was to explore the association between psychological stress and sleep and to identify if specific aspects of sleep are disturbed.